Development and application of a TaqMan-based real-time PCR method for the detection of the ASFV MGF505-7R gene - Qi, Chuanxiang; Zhang, Yongqiang; Wang, Zhenzhong; Li, Jinming; Hu, Yongxin; Li, Lin; Ge, Shengqiang; Wang, Qinghua; Wang, Yingli; Wu, Xiaodong; Wang, Zhiliang (Frontiers in Veterinary Science, 2023)
African swine fever virus (ASFV), the aetiological agent of African swine fever (ASF), results in deadly hemorrhagic fever in domestic pigs. ASF's high mortality and morbidity had disastrous effects on the world's swine industry. In recent years, the number of African swine virus strains has increased and put forward new challenges for classical ASFV-p72 based detection. Here we noticed ASFV MGF505-7R gene, a member of multigene family that can enhance ASFV virulence and pathogenesis which have potential to be the candidate for vaccine formulations. In this study, we developed a real-time PCR assay based on the ASFV MGF505-7R gene and validated it from multiple aspects. Results indicated that the approach could identify standard plasmid with sensitivity and specificity of up 1×101 copies/μL, moreover, the assay had no cross-reactions with other porcine viruses. For laboratory study and clinical diagnosis, the assay can detect ASFV infected samples at an early stage at 4hpi and show consistency of 92.56% when compared with classical ASFV detection in clinical ASFV-infected materials. Our data demonstrate that the developed ASFV MGF505-7R TaqMan based Quantitative Real-time PCR assay for the ASFV MGF505-7R offers a sensitive and specific approach for the quick and accurate detection of the ASFV, showing promise as an optional detection scheme for the purpose of screening and surveillance of ASF.